2018
DOI: 10.1002/jcb.27164
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA GIHCG enhanced tongue squamous cell carcinoma progression through regulating miR‐429

Abstract: Long noncoding RNAs play essential roles in cancer development and progression. Here, we tried to investigate the role of GIHCG in the progression and metastasis of tongue squamous cell carcinoma (TSCC). In our study, we showed that that the expression level of GIHCG was upregulated in TSCC tissues and cell lines. In addition, we indicated that high GIHCG expression was positively associated with poor overall survival. Moreover, ectopic expression of GIHCG enhanced TSCC cell cycle, proliferation, and migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Univariate Kaplan–Meier analyses also found the expression of several other lncRNAs to be positively correlated with poorer survival in OSCC including MALAT1 ( p < 0.05, 54 patients) (Zhou et al., ), NEAT1 ( p = 0.042, 58 patients and p = 0.01, 30 patients) (Huang, He, et al., ; Liu, Shang et al., ), LINC00668 ( p < 0.05, 50 patients) (Zhang, ), FTH1P3 ( p = 0.0032, 70 patients) (Zhang, ), CCAT2 ( p = 0.028, 62 patients) (Ma et al., ), PDIA3P ( p = 0.0211, 58 patients) (Sun et al., ) and ANRIL ( p = 0.013, 130 patients) (Chai, Yuan, Chen, Zhou, & Wu, ). When analysing only TSCC patients, higher expression associated with poor OS was found for GIHCG ( p < 0.05 from a 20 patients cohort) (Ma, Wang, Gong, Xue, & Zuo, ). Conversely, an underexpression of PTENp1 ( p = 0.04, 62 patients) (Gao et al., ) and LINC01133 ( p = 0.013, 50 patients) (Kong et al., ) correlated with a reduced survival rate.…”
Section: De Lncrnas and Clinicopathological Featuresmentioning
confidence: 99%
“…Univariate Kaplan–Meier analyses also found the expression of several other lncRNAs to be positively correlated with poorer survival in OSCC including MALAT1 ( p < 0.05, 54 patients) (Zhou et al., ), NEAT1 ( p = 0.042, 58 patients and p = 0.01, 30 patients) (Huang, He, et al., ; Liu, Shang et al., ), LINC00668 ( p < 0.05, 50 patients) (Zhang, ), FTH1P3 ( p = 0.0032, 70 patients) (Zhang, ), CCAT2 ( p = 0.028, 62 patients) (Ma et al., ), PDIA3P ( p = 0.0211, 58 patients) (Sun et al., ) and ANRIL ( p = 0.013, 130 patients) (Chai, Yuan, Chen, Zhou, & Wu, ). When analysing only TSCC patients, higher expression associated with poor OS was found for GIHCG ( p < 0.05 from a 20 patients cohort) (Ma, Wang, Gong, Xue, & Zuo, ). Conversely, an underexpression of PTENp1 ( p = 0.04, 62 patients) (Gao et al., ) and LINC01133 ( p = 0.013, 50 patients) (Kong et al., ) correlated with a reduced survival rate.…”
Section: De Lncrnas and Clinicopathological Featuresmentioning
confidence: 99%
“…13 In addition, GIHCG has been reported to be overexpressed in and promote tumor progression of renal cell carcinoma, tongue squamous cell carcinoma, ovarian cancer, cervical cancer, breast cancer, colorectal cancer and gastric cancer. [14][15][16][17][18][19][20][21] We hypothesized that GIHCG may act as an oncogene during tumorigenesis, however the prognostic value of GIHCG and its possible biological functions in HCC have yet to be fully assessed. Our study aims to assess the prognostic value of GIHCG in both the public HCC database and our clinical HCC cohort and to explore potential pathway correlations with GIHCG expression.…”
Section: Introductionmentioning
confidence: 99%
“…They are implicated in the modulation of gene expression at the pre-transcriptional, transcriptional and post-transcriptional levels (10). A change in lncRNA expression has been identified in a variety of human cancer types, including gastric cancer (11), thyroid cancer (12), hepatocellular carcinoma (13) and TScc (14). Regarding TScc, recent studies have indicated that numerous lncRNAs are abnormally expressed in this type of tumor and act as either tumor-suppressors or oncogenic RNAs (15,16).…”
Section: Introductionmentioning
confidence: 99%